Introduction to Law, 2nd ed. - Hage, Jaap (Springer, 2022)
This book is exceptional in the sense that it provides an introduction to law in general rather than the law of one specific jurisdiction, and it presents a unique way of looking at legal education. It is crucial for lawyers to be aware of the different ways in which societal problems can be solved and to be able to discuss the advantages and disadvantages of different legal solutions. In this respect, being a lawyer involves being able to reason like a lawyer, even more than having detailed knowledge of particular sets of rules. Introduction to Law reflects this view by focusing on the functions of rules and on ways of arguing the relative qualities of alternative legal solutions. Where ‘positive’ law is discussed, the emphasis is on the legal questions that must be addressed by a field of law and on the different solutions which have been adopted by, for instance, the common law and civil law tradition. The law of specific jurisdictions is discussed to illustrate possible answers to questions such as when the existence of a valid contract is assumed.